The Historical and Educational Conditions of the Emergence of Modernist Schools in Bukhara - Gulboyev Akbar Tukhtaevich; Khakimov Shukhrat Shodievich (International Journal on Integrated Education, 2023)
To study the historical and educational conditions of the emergence of Jadidist schools in Bukhara in the process of educating students.